The Progress In Research Ontargeted And Immunotherapy For Non-Small Cell Lung Cancer - Qian Zijia (BIO Web of Conferences)
The incidence and mortality rates of non-small cell lung cancer (NSCLC) are alarmingly high, positioning it as one of the most critical diseases that require immediate attention. This paper first outlines the current status of NSCLC, followed by a discussion of traditional treatment modalities, including surgery, chemotherapy, and radiotherapy, as well as emerging options such as targeted therapy and immunotherapy. Finally, it offers a summary and outlook on the overall landscape of NSCLC treatment, emphasizing the belief that ongoing and in-depth research on NSCLC will continually benefit affected patients.